A construção de tesauros com a integração de procedimentos terminográficos - Cervantes, Brígida Maria Nogueira [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
It investigates the terminographic integration for the thesauri construction in the search of terminographic procedures that may be used together with existing methodological procedures of subject analysis, for the improvement of the concepts representation in the thesauri construction. It is a theoretical-methodological study of the thesauri construction, focusing in the concepts identification in specialized area for the representation and thematic information retrieval. The general purpose of this research is to conceive a methodological model for the thesauri construction with the terminographic procedures integration. The specific purposes are to analyze and synthesize theoretical-methodological framework on thesauri construction, identify the main theoretical-methodological aspects of Terminology/Terminography which contribute to the thesauri construction, and present a proposal of a terminographic methodological model for the thesaurus construction. The research methodology is bibliographical, descriptive and exploratory, focusing on the thematic approach of vocabulary of speciality areas. It emphasizes as a result of this work, the “Preliminary Terminographic Thesauri in Information Management”, available in the web. It concludes that the improvement of thesauri construction stages, with the contributions of terminographic procedures, produce a concepts representation, by means of terms, having in mind the acquisition of a consistent vocabulary, which forms the basis for the organization and thematic information retrieval, and compatible with the demand of specialized areas.

Investiga a integração da Terminografia para a construção de tesauros na busca de procedimentos terminográficos que podem ser aplicados em conjunto com procedimentos metodológicos existentes de análise de assunto, para o aprimoramento da representação de conceitos na construção de tesauros. Realiza um estudo teórico-metodológico da construção de tesauro, com enfoque na identificação de conceitos em áreas de especialidade para a organização e recuperação temática da informação. Apresenta como objetivo geral enunciar um modelo metodológico para a construção de tesauro com a integração de procedimentos terminográficos. Como objetivos específicos: analisar e sintetizar referenciais teórico-metodológicos sobre construção de tesauros; identificar os principais aspectos teórico-metodológicos da Terminologia/Terminografia contribuintes para a construção de tesauros; e apresentar proposta de um modelo metodológico terminográfico para a construção de tesauros. A metodologia da pesquisa qualifica-se por sua natureza bibliográfica, descritiva e exploratória, concentrando-se na abordagem temática do vocabulário de áreas de especialidade. Enfatiza como um resultado do trabalho aplicado o “Tesauro Terminográfico Preliminar em Gestão da Informação”, disponível na web. Conclui que o aprimoramento de etapas da construção de tesauro, aliado a contribuições de procedimentos terminográficos, produz uma representação de conceitos, por meio de termos, tendo em vista a obtenção de um vocabulário consistente, que compõe a base para a organização e recuperação temática da informação, e compatível com a demanda de áreas de especialidade.
Keywords: Tesauros; Linguagem documentária; Terminografia; Linguagens documentárias alfabéticas; Thesaurus construction; Terminography; Terminographic thesauri